Angular vortex phase diagram in YBa2Cu3O7 films with c-axis correlated pinning centers. (1st July 2021) - Horide, Tomoya; Ichino, Yusuke; Matsumoto, Kaname
Abstract: High temperature superconductors (HTSCs) exhibit rich vortex phases under the influence of nanoscale pinning centers, and complicated configurations and behavior of vortices are realized by anisotropic vortex pinning, vortex interaction, and line tension. To understand the behavior and configurations of vortices, YBa2 Cu3 O7 films containing self-organized nanorods (BaSnO3, BaZrO3, BaHfO3 ) were prepared, and the critical current density and the resistivity were measured for varying angles between the nanorods (// c -axis) and the magnetic field ( θ ) in the temperatures of 65–90 K. The trapping angle of the strong nanorod ( θ ts ) determines the vortex phase boundary in the magnetic field lower than the matching field ( B < B ϕ ). While the large c -axis J c peak and the resistivity dip are observed for θ < θ ts due to the vortex accommodation on the nanorods, the vortices for θ > θ ts are pinned by the matrix uncorrelated defects and/or the ab -plane pinning centers. In the magnetic field higher than B ϕ ( B > B ϕ ), the weak matrix c-axis correlated defects such as twin boundaries accommodate vortices at the angles smaller than the trapping angle of the matrix c-axis correlated defect. Although the matrix c-axis correlated defects do not pin the matrix-vortices for the larger angles, the matrix-vortices are pinned by the vacant nanorod portions that appear due to the magnetic field tilt. This vortex retrapping results in the off-axis J c peak and the off-axis resistivity dip. Thus, the weak pinning by matrix defects, the cage potential, and the vortex retrapping as well as the strong nanorod pinning determine the angular vortex phase of the HTSCs containing c -axis correlated pinning centers.